Classroom Management Practices of Secondary-Level English Teachers - Rajan Kumar Kandel; Ganesh Kumar Kandel; Samiksha Raskoti (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
Effective classroom management supports students’ learning engagement and facilitates their language acquisition. This study explores how secondary-level English teachers use various strategies to manage ELT classrooms effectively for enhancing student engagement, better learning, and fostering a positive learning environment. Four teachers from two secondary schools of Birendranagar Municipality were selected purposively as the participants of this study to explore their subjective experiences. The semi-structured interview guideline and classroom observation sheet were used to elicit data based on their experiences and practices. The collected data were coded and analysed thematically. The findings revealed that the teachers created a classroom organization plan for the management of the ELT classroom. The study also explored teachers’ classroom management strategies based on instructing students, conducting activities and managing the physical setting. The findings of the study imply that evidence-based effective classroom management practices used for maintaining classroom discipline and creating a culturally responsive English language learning environment inform training modules and resource allocation to enhance pedagogical efficiency.